Assessing benefits of slum upgrading programs in second-best settings - Dāśagupta, Bāsaba, 1958- 1958- (Policy research working paper, 2006)
"Slum upgrading programs are being used by national and city governments in many countries to improve the welfare of households living in slum and squatter settlements. These programs typically include a combination of improvements in neighborhood infrastructure, land tenure, and building quality. In this paper, the authors develop a dynamic general equilibrium model to compare the effectiveness of alternative slum upgrading instruments in a second-best setting with distortions in the land and credit markets. They numerically test the model using data from three Brazilian cities and find that the performance of in situ slum upgrading depends on the severity of land and credit market distortions and how complementary policy initiatives are being implemented to correct for these problems. Pre-existing land supply and credit market distortions reduce the benefit-cost ratios across interventions, and change the rank ordering of preferred interventions. In the light of these findings, it appears that partial equilibrium analysis used in typical cost-benefit work overstates the stream of net benefits from upgrading interventions and may in fact propose a misleading sequence of interventions. "--World Bank web site